Edukasi Pencegahan Anemia dan Peningkatan Kepatuhan Konsumsi Tablet Tambah Darah Pada Remaja Putri di Desa Pariti Kecamatan Sulamu Kabupaten Kupang - Ike Liani Stefani Zacharias; Maria Anjela Vedruna Kehi; Wilhelmina Angellica Oka; Matje Meriaty Huru; Namsyah Baso; Mariana Ngundju Awang; Agustina Abuk Seran; Melinda Rosita Wariyaka; Ni Luh Made Diah Putri Anggaraeningsih (Health Care : Journal of Community Service, 2025)
Anemia is a significant public health problem, especially in adolescent girls. The prevalence of anemia among adolescent girls globally is still high and is one of the main causes of low productivity and impaired physical and cognitive development. Adolescent girls are a vulnerable group to anemia because they menstruate every month and require higher iron intake. Anemia at this age can continue into pregnancy and increase the risk of pregnancy complications, premature birth, and low birth weight babies. This activity aims to increase adolescent girls' knowledge in efforts to prevent anemia and increase compliance in consuming Iron Supplement Tablets (TTD). The method used is through counseling. Partners in this activity are all adolescent girls in Pariti Village as many as 35 people. Knowledge evaluation uses pre-test and post-test questionnaires. The assessment results show that there is a difference in the average pre-test score of 67.4 (SD = 6.79) and the average post-test score of 89.1 (SD = 6.58). The results of statistical tests showed a significant increase in the knowledge of adolescent girls after being given educational materials about anemia and Iron Tablets (TTD) (p = 0.000; α < 0.05).